Analysing The Performance Efficiency of the Crop Insurance Scheme - Pradhan Mantri Fazal Bima Yojana in Cauvery Delta Zone of Tamil Nadu: Two – Stage Closed DEA Approach - D. Hebsiba Beula (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this study, we use Data Envelopment Analysis (DEA) to evaluate the efficacy of the Pradhan Mantri Fazal Bima Yojana (PMFBY) crop insurance program in Tamil Nadu’s Cauvery Delta Zone. Assessing these schemes is crucial for agricultural risk mitigation, a key part of rural development. The Cauvery Delta Zone, known for its agricultural productivity, includes regions like Ariyalur, Cuddalore, Nagapattinam, Preambular, Pudukkottai, Thanjavur, Thiruvarur, and Tiruchirappalli. Technical efficiency is measured, and variables affecting inefficiency are identified using DEA. This methodology helps us understand the relative performance of PMFBY across various districts of CDZ. The DEA analysis results present efficiency scores and valuation metrics for each Decision-Making Unit (DMU) over the five years of Kharif season (2018–2022) using data from the Agricultural Insurance Company.